Physiological work areas in professional beach volleyball players during competition matches (Zonas de trabajo en jugadores profesionales de vóley playa: Un caso de estudio) - José Manuel Jimenez Olmedo; Basilio Pueo; Alfonso Penichet Tomás; Juan José Chinchilla Mira; José Antonio Perez Turpin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2017)
In this paper, physiological areas of professional beach volleyball players are identified by combining notational analysis tools together with in-sync heart rate capture for specific time periods in competition games. The aim is to identify workload areas depending on the player´s position as well as the changes these areas undergo during real competitions. To this end, a case study is quantitatively analyzed and based on the Spanish National Team during the First International Training Tournament «Sixto Jimenez» played in Tenerife (Spain). Workload ranges differ between blocker player (from 77.71% to 89.13%) and defensive player (from 66.16% to 77.77%), both values are related to their individual HRmax. Furthermore, median HRmax values indicate that blocker player must support an increased workload of 84.78% compared to 71.71% of the defending player. Therefore, the specific position of the defenders established significant differences in their physiological responses